The psychology of evaluation : affective processes in cognition and emotion - Musch, Jochen; Klauer, Karl C. (Lawrence Erlbaum Associates, 2003)
The affective connotations of environmental stimuli are evaluated spontaneously and with minimal cognitive processing. The activated evaluations influence subsequent emotional and cognitive processes. Featuring original contributions from leading researchers active in this area, this book reviews and integrates the most recent research and theories on this exciting new topic. Many fundamental issues regarding the nature of and relationship between evaluations, cognition, and emotion are covered. The chapters explore the mechanisms and boundary conditions of automatic evaluative processes, the.